Correlation between excessive sugar intake and overactive bladder in children - Cui, Xu; Wei, Bo-Chao; Chen, Zhi-Qiang; Xu, Long-Yao; Yin, Bing-Qian; Zhou, Chao-Ming (Frontiers in Pediatrics, 2025)
PurposeThe aim of this study was to explore the relationship between excessive sugar intake and symptoms of paediatric overactive bladder (OAB).MethodsClinical data was collected from 97 patients diagnosed with OAB at our hospital between July 2024 and January 2025. The relationships between sugar intake and OAB symptom scores were analysed.ResultsA total of 97 children diagnosed with OAB were included in this study, with 78 (80.41%) exhibiting excessive sugar intake and 19 (19.59%) exhibiting non-excessive sugar intake. Patients in the excessive sugar intake group had a significantly longer duration of OAB symptoms compared to those in the non-excessive sugar intake group (P < 0.05). A comparison of OAB symptoms between the two groups revealed that patients in the excessive sugar intake group had significantly higher total scores on the overactive bladder symptom score (OABSS) and higher scores for daytime urinary frequency, urgency frequency, and urgency urinary incontinence compared to those in the non-excessive sugar intake group (P < 0.05). Correlation analysis between sugar intake and OAB symptoms revealed significant positive correlations between average daily total sugar intake and the symptom duration of OAB, OABSS total score, daytime urination frequency score, urgency frequency score, and urgency urinary incontinence score (P < 0.05). The duration of excessive sugar intake was significantly positively correlated with the symptom duration of OAB, OABSS total score, and urgency urinary incontinence score (P < 0.05). The average daily sugar intake from fruits was also significantly positively correlated with the symptom duration of OAB, OABSS total score, daytime urination frequency score, urgency frequency score, and urgency urinary incontinence score (P < 0.05).ConclusionExcessive sugar intake was closely associated with the severity of OAB symptoms in children. Both the quantity of sugar intake and the duration of excessive sugar intake were positively correlated with the severity of OAB symptoms. Among all types of sugary foods consumed, the average daily intake of fructose was positively correlated with the severity of OAB symptoms.